Adenovirus-based HIV-1 vaccine candidates tested in efficacy trials elicit CD8+ T cells with limited breadth of HIV-1 inhibition. (17th July 2016) - Hayes, Peter J.; Cox, Josephine H.; Coleman, Adam R.; Fernandez, Natalia; Bergin, Philip J.; Kopycinski, Jakub T.; Nitayaphan, Sorachai; Pitisuttihum, Punnee; de Souza, Mark; Duerr, Ann; Morgan, Cecilia; Gilmour, Jill W.
Abstract : Objectives: The ability of HIV-1 vaccine candidates MRKAd5, VRC DNA/Ad5 and ALVAC/AIDSVAX to elicit CD8 + T cells with direct antiviral function was assessed and compared with HIV-1-infected volunteers. Design: Adenovirus serotype 5 (Ad5)-based regimens MRKAd5 and VRC DNA/Ad5, designed to elicit HIV-1-specific T cells, are immunogenic but failed to prevent infection or impact on viral loads in volunteers infected subsequently. Failure may be due in part to a lack of CD8 + T cells with effective antiviral functions. Methods: An in-vitro viral inhibition assay tested the ability of bispecific antibody expanded CD8 + T cells from peripheral blood mononuclear cells to inhibit replication of a multiclade panel of HIV-1 isolates in autologous CD4 + T cells. HIV-1 proteins recognized by CD8 + T cells were assessed by IFNγ enzyme-linked immunospot assay. Results: Ad5-based regimens elicited CD8 + T cells that inhibited replication of HIV-1 IIIB isolate with more limited inhibition of other isolates. IIIB isolate Gag and Pol genes have high sequence identities (>96%) to vector HIV-1 gene inserts, and these were the predominant HIV-1 proteins recognized by CD8 + T cells. Virus inhibition breadth was greater in antiretroviral naïve HIV-1-infected volunteers naturally controlling viremia (plasma viral load < 10 000/ml). HIV-1-inhibitory CD8 + T cells were not elicited by the ALVAC/AIDSVAX regimen. Conclusion: The Ad5-based regimens, although immunogenic, elicited CD8 + T cells with limited HIV-1-inhibition breadth. Effective T-cell-based vaccines should presumably elicit broader HIV-1-inhibition profiles. The viral inhibition assay can be used in vaccine design and to prioritize promising candidates with greater inhibition breadth for further clinical trials. Abstract : Supplemental Digital Content is available in the text